2016
DOI: 10.1038/srep24397
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant soluble gp130 protein reduces DEN-induced primary hepatocellular carcinoma in mice

Abstract: IL-6 (interleukin 6) plays an important role in the development and growth of hepatocellular carcinoma (HCC) via both classic signaling and trans-signaling pathways. Soluble gp130 (sgp130) is known to be a natural inhibitor of the trans-signaling pathway. In the present study, our goal was to investigate whether recombinant sgp130 could suppress the initiation and progression of HCC in mouse models. Our results demonstrate that sgp130 induced an apoptosis of HepG2 cells and inhibited the clonogenicity of HepG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 40 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Our present study strongly suggests that use of recombinant sgp130Fc would target multiple steps of hepatocarcinogenesis without compromising immune function and therefore represents a novel therapeutic option for adjuvant treatment of HCC or to prevent relapse after HCC surgery. During manuscript preparation, a brief report appeared showing that recombinant sgp130Fc was able to suppress HepG2 tumor growth in immune‐deficient mice, however without investigation of the underlying mechanism . A recent phase I clinical study has shown that recombinant sgp130Fc is well tolerated in humans .…”
Section: Discussionmentioning
confidence: 99%
“…Our present study strongly suggests that use of recombinant sgp130Fc would target multiple steps of hepatocarcinogenesis without compromising immune function and therefore represents a novel therapeutic option for adjuvant treatment of HCC or to prevent relapse after HCC surgery. During manuscript preparation, a brief report appeared showing that recombinant sgp130Fc was able to suppress HepG2 tumor growth in immune‐deficient mice, however without investigation of the underlying mechanism . A recent phase I clinical study has shown that recombinant sgp130Fc is well tolerated in humans .…”
Section: Discussionmentioning
confidence: 99%
“…In our experimental designs, the gp130 antibody, gp130 shRNA and IL-6 antibody are used as the blockers of the entire IL-6 signalling events, both the classic and trans-signalling. Meanwhile, IL-6R shRNA is applied to interrupt the classic signalling of IL-6 and the sgp130, a natural receptor of IL-6-sIL-6R complex competitively preventing their binding with the membrane-bound gp130, is applied to block IL-6 trans-signalling without affecting the classic signalling [34][35][36][37][38]. Our data show that simultaneously inhibiting both classic and trans-signalling markedly minimizes HG-induced podocyte injury, presenting as the reduced desmin levels as well as the attenuated Factin loss and rearrangement.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is currently ranked among the most common primary malignant cancers worldwide and is the third and fifth leading cause of death from cancer globally in men and women, respectively123. Due to lack of effective strategies for early diagnosis and pre-clinical screening for HCC in high-risk populations, the majority of patients can be treated only with loco regional therapies, resulting in limited survival benefits and tumor recurrence in 50–80% of patients at 5 years after treatment45.…”
mentioning
confidence: 99%